EFEKTIVITAS AUDIT INTERNAL: ANALISIS FAKTOR BUDAYA HOFSTEDE, FAKTOR KARAKTERISTIK INDIVIDUAL AUDITOR, DAN EFEK MODERASI DUKUNGAN MANAJEMEN (Studi pada Bank Riau Kepri) - Chen Kelly; Anugerah Rita; Rasuli M (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2022)
This study draws on Hofstede’s theoretical framework and individual characteristics with management support as moderation effect to examine the impact on the internal audit effectiveness. The data collection technique used in this study is questionnaire with Likert scale to 51 Bank Riau Kepri Internal Auditors to examine the effect of the cultural dimensions of power distance, uncertainty avoidance, individualism, individual characteristics and management support on the internal audit effectiveness. Warp PLS 7.0 Statistical test results showed that individual characteristics, uncertainty avoidance, and individualism have significant effect on the internal audit effectiveness, power distance has no significant effect on the internal audit effectiveness, and management support is unable to moderate the individual characteristic on the internal audit effectiveness.Keywords: Individual Characteristics, Management Support, Hofstede Theoretical Framework, Power Distance, Uncertainty Avoidance, Individualism